HANDLING GUEST CHECK OUT AT HARRIS RESORT WATERFRONT BATAM - Firma Hillari Izzah; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Batam City is one of the areas in the Riau Archipelago province where economic development is progressing rapidly. One of the supporting factors is that Batam City is the main route for tourists to enter and exit, as well as trade routes. As a stopover for tourists, this naturally makes Batam City ready to provide decent and comfortable accommodation. In a hotel, the front office is the department that deals directly with guests, from guests who book rooms to guests who want to leave the hotel. Front Office is the first impression and the last impression guests will always remember. As for the Front Office, HARRIS Resort Waterfront Batam takes good care of the guests to make a good impression also when handling the departure or checkout of guests. The purpose of this study was to determine the handling of guest checkout and check-out SOPs. Based on the method used in this study, it is qualitative to find out the results of the study through observation, interviews with the Harris Resort Waterfront Batam Front Office and guests staying, as well as documentation with sources who provided answers . Based on surveys and interviews conducted by the author, it can be concluded that the Check-out Handling at HARRIS Resort Waterfront Batam went well, also the Standard Operational Procedure (SOP) in the check-out process was carried out by all employees of the Front Office department. Keyword: check out, Front Office, Hotel